Sensorimotor dysfunction and postural instability in older adults with type 2 diabetes mellitus: the role of proprioception and neuropathy - Kardm, Saleh M.; Kardm, Abdulmohsen Saeed; Alanazi, Ziad Ahmed; Alnakhli, Hani Hassan; Alkhamis, Batool Abdulelah; Reddy, Ravi Shankar (Frontiers in Aging Neuroscience, 2025)
BackgroundType 2 diabetes mellitus (T2DM) is associated with proprioceptive impairment and postural instability, contributing to increased fall risk. The role of glycemic status and peripheral neuropathy in these deficits remains under-characterized using objective measurement tools.ObjectivesTo compare ankle joint proprioception and postural stability between individuals with T2DM and healthy controls using dual inclinometry and computerized posturography, and to examine the relationship between these impairments and glycemic control (HbA1c). Additionally, to evaluate the impact of peripheral neuropathy on sensorimotor function.MethodsA cross-sectional study included 66 individuals with T2DM and 66 age- and sex-matched healthy controls. Ankle joint proprioception was assessed using dual digital inclinometers, which quantify joint position sense errors during dorsiflexion and plantarflexion. Postural stability was evaluated via posturography under eyes-closed conditions, measuring sway area, velocity, and center of pressure (CoP) displacement.ResultsParticipants with T2DM showed significantly greater proprioceptive errors in dorsiflexion (mean difference = 1.93°, 95% CI: 1.61–2.26, d = 2.06) and plantarflexion (mean difference = 2.50°, 95% CI: 2.08–2.92, d = 2.03) compared to controls. Postural sway area and velocity were also higher (sway area mean difference = 62.76 cm2, 95% CI: 47.44–78.07, d = 1.40). HbA1c levels were moderately correlated with proprioception errors (r ≈ 0.54) and postural instability (r ≈ 0.65). Participants with peripheral neuropathy demonstrated significantly worse proprioception and balance. Regression models showed HbA1c and diabetes duration were significantly associated with proprioceptive and postural impairments (adjusted R2: 0.29–0.48 for both domains).ConclusionIndividuals with T2DM, particularly those with poor glycemic control or peripheral neuropathy, show greater sensorimotor deficits. These findings support early proprioceptive screening and balance interventions to reduce fall risk in diabetic populations. All associations should be interpreted within the limitations of a cross-sectional design.